2003
DOI: 10.1080/15287390306409
|View full text |Cite
|
Sign up to set email alerts
|

Benzo[a]Pyrene Diones are Produced by Photochemical and Enzymatic Oxidation and Induce Concentration-Dependent Decreases in the Proliferative State of Human Pulmonary Epithelial Cells

Abstract: Organic components within mixtures of combustion-derived materials may play an important role in the correlation between air pollution and adverse cardio/respiratory health. One class of these organic components, polycyclic aromatic hydrocarbons (PAHs), has been shown to produce a wide variety of adverse health effects. An air toxic and a model PAH, benzo[a]pyrene (BaP), is a component of combustion-derived particulate matter (PM). Although most biological effects associated with BaP have been attributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…4C). Decreased kinase activity in monolayer cultures observed in the current study is a reflection of the growth inhibitory properties of BaP (9,21,62,64,65). Analysis of growth curves over the 7-day period revealed that the viability of cells in the BaP-treated monolayers was dramatically decreased compared with DMSO controls (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…4C). Decreased kinase activity in monolayer cultures observed in the current study is a reflection of the growth inhibitory properties of BaP (9,21,62,64,65). Analysis of growth curves over the 7-day period revealed that the viability of cells in the BaP-treated monolayers was dramatically decreased compared with DMSO controls (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Previously, incubation of B[a]P with arachidonic acid and ram seminal vesicles resulted in the formation B[a]P-1,,6-, 3,6-, and 6,12-diones on the same time course as prostaglandin (PG)H 2 production suggesting that B[a]P acts as a co-reductant in the peroxidase cycle of PGH synthase (53). Other peroxidases implicated in the formation of these diones are lactoperoxidase (an airway peroxidase) (54).…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous reports that photooxidation of PAHs in the environment produces oxygenated PAHs and PAH quinones [55,[74][75][76][77][78][79][80]. A number of reviews have reported photooxidation and photodegradation of PAHs in the environment [81][82][83][84].…”
Section: A Formation Of Oxygenated Pahs and Pah Quinonesmentioning
confidence: 99%